The Influence of Asset Management, Liquidity, and Working Capital Turnover on Financial Performance - Putri, Adisty Syifa Firdaus; Murti, Galuh Tresna (Husnayain Business Review, 2024)
This study aims to test the impact of asset management (TATO), liquidity (CR), and working capital turnover (WCTO) on financial performance (ROA) with the research objects of real estate and property sector companies listed on the Indonesian Stock Exchange and the period 2018-2022. Methodology/approach – The type of this research is quantitative with panel data regression analysis. The sampling technique used purposive samplings so 63 companies were obtained with a research period of 5 years. Findings – It was found that simultaneous asset management, liquidity, and working capital turnover influence financial performance. Partially asset management has a positive impact on financial performance. While liquidity and working capital turnover have no influence on financial performance. Novelty/value – As the property and real estate sector is an important sector because it can provide a multiplier effect, then it must have good financial performance so it is necessary to know what factors can affect financial performance.